Sobre el etnónimo de los gálatas (y de los celtas) - Ballester, Xaverio (Gerión. Revista de Historia Antigua, 2002)
Some of the traditional explanations for the name of the Celtae have no typological paralell at all. The old name of the Celtae could be well preserved in the ethnonym Galatai, which could be explained as *gala- ´end, limit, border´ and *tai `those, they´ with the general meaning of `the border people´, a common kind of ethnonym that suits the geographical situation of old Celts and their historical background.